ChemInform Abstract: Benzofuran and Indole Synthesis via Cu(I)‐Catalyzed Coupling of N‐Tosylhydrazone and o‐Hydroxy or o‐Amino Phenylacetylene. Issue 29 (1st July 2013) - Xiao, Tiebo; Dong, Xichang; Zhou, Lei
Abstract: Title compounds (III), (V), and (VII) are prepared via a CuBr‐catalyzed coupling‐allenylation‐cyclization sequence under ligand‐free conditions.